Impact of point-of-care C reactive protein in ambulatory care: a systematic review and meta-analysis. Issue 1 (1st February 2019) - Verbakel, Jan Y; Lee, Joseph J; Goyder, Clare; Tan, Pui San; Ananthakumar, Thanusha; Turner, Philip J; Hayward, Gail; Van den Bruel, Ann
Abstract : Objective: The aim of this review was to collate all available evidence on the impact of point-of-care C reactive protein (CRP) testing on patient-relevant outcomes in children and adults in ambulatory care. Design: This was a systematic review to identify controlled studies assessing the impact of point-of-care CRP in patients presenting to ambulatory care services. Ovid Medline, Embase, Cochrane Database of Systematic Reviews, Cochrane CENTRAL, DARE, Science Citation Index were searched from inception to March 2017. Eligibility criteria for selecting studies: Controlled studies assessing the impact of point-of-care CRP in patients presenting to ambulatory care services, measuring a change in clinical care, including but not limited to antibiotic prescribing rate, reconsultation, clinical recovery, patient satisfaction, referral and additional tests. No language restrictions were applied. Data extraction: Data were extracted on setting, date of study, a description of the intervention and control group, patient characteristics and results. Methodological quality of selected studies and assessment of potential bias was assessed independently by two authors using the Cochrane Risk of Bias tool. Results: 11 randomised controlled trials and 8 non-randomised controlled studies met the inclusion criteria, reporting on 16 064 patients. All included studies had a high risk of performance and selection bias. Compared with usual care, point-of-care CRP reduces immediate antibiotic prescribing (pooled risk ratio 0.81; 95% CI 0.71 to 0.92), however, at considerable heterogeneity (I 2 =72%). This effect increased when guidance on antibiotic prescribing relative to the CRP level was provided (risk ratios of 0.68; 95% CI 0.63 to 0.74 in adults and 0.56; 95% CI 0.33 to 0.95 in children). We found no significant effect of point-of-care CRP testing on patient satisfaction, clinical recovery, reconsultation, further testing and hospital admission. Conclusions: Performing a point-of-care CRP test in ambulatory care accompanied by clinical guidance on interpretation reduces the immediate antibiotic prescribing in both adults and children. As yet, available evidence does not suggest an effect on other patient outcomes or healthcare processes. PROSPERO registration number: CRD42016035426; Results.